PENGARUH KETERAMPILAN WIRAUSAHA DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KEBERHASILAN USAHA PADA PELAKU USAHA KECIL DI PASAR BUNGA BRATANG SURABAYA - Tariza Ramadhania; Diana Juni Mulyati; Sri Andayani (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
The development of UMKM competitiveness is currently strongly influenced by various factors, in which human resources play such an important role. During the Covid-19 pandemic, some people found new habits to overcome boredom, including planting ornamental plants. Since the pandemic and the trend of ornamental plants came suddenly, the popularity of ornamental plants has increased sharply, which means this is profitable for ornamental plant businesses. The importance of knowledge and experience regarding proper plant care techniques, as well as the importance of interacting with consumers are important factors in achieving business success. At the writing of this study, the authors completed research on Entrepreneurial Skills and Human Resource Competence on Business Success. The method used in this study is a quantitative method using census techniques or side saturation, meaning that all population groups are used as samples. Data sources in this research are primary data sources and secondary data sources. The data analysis technique used is multiple linear regression analysis. In the final results of the research, it proves that from the t test and F test that have been carried out, it can be seen that the Entrepreneurial Skills and Human Resource Competency variables partially and simultaneously or jointly have a positive and significant effect on business success for small business actors in the Flower Market Bratang Surabaya. In order to advance the Skills and Competence of Human Resources, it is necessary to have training, experience, and by learning various planting techniques. In addition, the importance of communicating and interacting with consumers in maintaining relationships.